Anti-harassment policies across Canadian and international medical programs: Strengths, areas for improvement, and a need for standardization - Peters, Hannah; Ahn, Byunghoon; Gong, Ruilin; Lou, Nigel Mantou; Harley, Jason M (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2025)
Background/Purpose: Medical trainee harassment is a global issue that has led to a multitude of detrimental effects. An important area of consideration is whether harassment policies are clear and available to all medical trainees globally. We aimed to develop a standardized rubric for evaluating anti-harassment policies and assess policies across Canadian medical schools and top international universities to identify strengths and areas for improvement.Methods: We constructed a rubric by synthesizing criteria from established frameworks on harassment policy effectiveness, adapting key elements to assess clarity, accessibility, and comprehensiveness in medical school policies. On March 2023, we evaluated 58 harassment policies from 16 Canadian medical schools and 31 policies from eight of the top 10 Quacquarelli Symonds (QS)-ranked universities. Our rubric, developed from four key frameworks, scored policies across three themes: (1) Policy Foundation, (2) Complaint Procedures, and (3) Resolution and Implementation.Results: Canadian universities performed well in foundational policy areas (average score 83.00% on Theme 1) but showed meaningful gaps in Complaint Procedures (48.75%) and Resolution and Implementation (39.38%). Top international QS-ranked universities similarly scored low in these latter themes, though they performed better on formal complaint processes. Key areas needing improvement include informal complaint procedures and timelines for response in Canadian universities, and policy revision commitments in top QS-ranked universities.Conclusions: This study highlights the need for enhanced anti-harassment policies, particularly in complaint and resolution procedures. Our rubric provides a structured approach for policy evaluation, enabling Canadian and potentially international institutions to improve policy clarity, accessibility, and comprehensiveness, fostering safer training environments.